Effect of elite sport activity on salivary microbiota: The case of water polo - Iolanda Veneruso; Cristina Mennitti; Alessandro Gentile; Gennaro Di Bonito; Jacopo Ulisse; Carmela Scarano; Barbara Lombardo; Daniela Terracciano; Raffaela Pero; Giovanni D'Alicandro; Giulia Frisso; Valeria D'Argenio; et al. (Heliyon)
It has been well established that the human gut microbiota plays a pivotal role in humans' health, since it is involved in nutrients' uptake, vitamins' synthesis, energy harvest, inflammatory modulation, and host immune responses. Moreover, gut microbiota alterations have been associated to an increasing number of diseases and its composition can be affected by several factors, including physical exercise. In particular, it has been reported that intense physical activity can induce metabolic changes which translate in alterations of specific biomarkers that can lead to the onset of infections, inflammation and hepatic or kidney disorders. Recently, the oral microbiota has shown its relevance not only for the health of oral cavity but also for human host's health, emerging as an ecological niche with a great potential for the study of gut microbiome alterations due also to its accessibility respect to other tracts that can be inferred through fecal samples analysis. Thus, the purpose of this study has been to assess the effect of intense physical activity, i.e., elite water polo, on the human salivary microbiota. Thirteen professional water polo players and nineteen sedentary controls were recruited for this study. The salivary microbiota analysis was performed in oral rinse collected from both controls and athletes three months after the beginning of the agonist season. Our results showed significant differences in the salivary microbiota between athletes and controls. In particular, three species, namely Oribacterium sinus, Oribacterium parvum and Oribacterium asaccharolyticum, were found to be significantly increased in the water polo players compared to controls. Even if these data have to be further validated, also to assess the role of these identified species, they strengthen the hypothesis that elite sports can influence and alter the status of the gut microbiota. Moreover, the saliva is confirmed as a suitable sample for microbiome evaluations that may improve athletes' status evaluation and monitoring.